1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Boolean Algebra

  1. Sep 5, 2007 #1
    1. The problem statement, all variables and given/known data

    F = A'C' + A'BC + B'C

    3. The attempt at a solution

    I put the above equation into a k-map and it simplified down to F = A' + B'C. Pretty easy.

    Well, after looking at the equation, that would seem to require that (C'+BC) = 1 since F = A'(C'+B'C) + B'C. However, if C = 1 and B = 0, then C'+BC = 0.

    Can anyone see where I went wrong?
    Last edited: Sep 6, 2007
  2. jcsd
  3. Sep 5, 2007 #2
    It is F = A'(C'+BC) + B'C
    NOT F = A'(C'+BC) + BC
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook